Antaseden dan Konsekuensi dari Attachment - Gita Amanda; Arwini Sumardi (Journal on Education, 2023)
This study is intended to analyze the antecedents and consequences of attachment. This research method is descriptive quantitative which is used to describe the relationship or influence toward research variables based on the use of statistical analysis and mathematical equations. The data source was obtained through an online questionnaire survey of 150 respondents as beauty influencer. The data analysis method used is the Structural Equation Model (SEM) to test the hypotheses in the study. The results of the study show that there is a positive effect of homophily, social presence, physical attractiveness on attachment, and there is a positive effect of attachment on loyalty to the influencer.